The Physical Properties and Morphologies of Faint Dusty Star-forming Galaxies Identified with JWST - S. J. McKay; A. J. Barger; L. L. Cowie; M. J. Nicandro Rosenthal (The Astrophysical Journal)
We identify a sample of 234 dusty star-forming galaxies (DSFGs) in the A2744 and GOODS-S fields using JWST/NIRCam-selected galaxies as priors for SCUBA-2 measurements. This method provides a large number of galaxies both above an 850 μ m flux of 2 mJy (47 bright DSFGs) and below (187 faint DSFGs), representing the largest sample of individually identified (i.e., not stacked) faint DSFGs to date. We observe that f _F444W and f _F150W are tightly correlated with redshift, with fainter sources lying at higher redshifts, suggesting that the observed near-IR flux may be an effective way of selecting high-redshift DSFGs. We study the physical properties and morphologies of the DSFGs through spectral energy distribution fitting and parametric surface brightness profile modeling. Other than the lower star formation rates (SFRs) and total infrared luminosities in the faint DSFGs (SFR $=\,8{0}_{-45}^{+81}$ ; ${L}_{{\rm{IR}}}=11.8{2}_{-0.36}^{+0.30}$ ) compared to the bright DSFGs (SFR $=\,25{4}_{-131}^{+135}$ ; ${L}_{{\rm{IR}}}=12.3{2}_{-0.30}^{+0.20}$ ), the populations have similar properties. The stellar masses do not appear to be strongly dependent on either the SFRs or the submillimeter flux. These results suggest that the faint DSFGs are drawn from the same population of galaxies as the bright DSFGs. Based on visual inspections, we find a lower merger fraction (∼21%) relative to previous Hubble Space Telescope–based studies, suggesting that dust attenuation may have impacted previous estimates of DSFG merger rates.